2019
DOI: 10.1088/1742-6596/1349/1/012098
|View full text |Cite
|
Sign up to set email alerts
|

Performance of porous asphalt pavement using clay brick dust as mineral filler

Abstract: High demand of recycling waste materials are able to solve disposal problem which created opportunities for researcher to use it in their product. Waste clay brick dust is one of the material can be improvised to be tested for the performance of porous asphalt pavement towards rutting problem. In this study, crushed dust of clay brick was used in porous asphalt mixture as mineral filler. 15 samples were produced in different proportions (4%, 4.5%, 5%, 5.5% and 6%) of bitumen content and each proportion have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The tests performed on asphalt concrete asphalt mix type also proved to have higher resistance to permanent deformation with the use of brick dust filler [26]. On the other hand, porous asphalt with the addition of brick dust was characterized by a deeper rut compared to a mixture with lime filler [27]. Differences in test results may result from the use of different testing procedures as well as differences in the properties of individual materials.…”
Section: Introductionmentioning
confidence: 97%
“…The tests performed on asphalt concrete asphalt mix type also proved to have higher resistance to permanent deformation with the use of brick dust filler [26]. On the other hand, porous asphalt with the addition of brick dust was characterized by a deeper rut compared to a mixture with lime filler [27]. Differences in test results may result from the use of different testing procedures as well as differences in the properties of individual materials.…”
Section: Introductionmentioning
confidence: 97%
“…Another investigation was conducted to evaluate the performance porous asphalt mixtures using clay brick dust as mineral filler. The results showed that the modified mixtures enhanced the binder draindown as it decreased from 0.3% for the conventional porous mixtures to 0.08%, but the presence of clay brick dust resulted in a reduction in the ability of resisting the rutting 8 . A Bottom Ash boiler was investigated as filler to the porous asphalt mixture with cement and it was concluded that a 6% asphalt content with a variation of filler 50% cement and 50% bottom ash boiler met the Australian Asphalt Pavement Association AAPA 2004 Specifications 9 .…”
Section: Introductionmentioning
confidence: 99%
“…), the remaining polymer carbohydrates can also be used to create bio-asphalt. Some researchers use soil as a modifier, such as nano clay [ 14 ], diatomite [ 15 , 16 ], organically modified bentonite [ 17 , 18 ] and so on. Take bentonite as an example.…”
Section: Introductionmentioning
confidence: 99%